Usefulness of absorption techniques in doubtful cases of incompatibility Rh maternal fetal: a case report - Eleonora Donno; Jessica Di Monte; Manuela Di Mascio; Tiziana Orsini; Annalisa Di Valerio; Luisa Pinti; Paola Massaro; Seila Scardapane; Francesca Fusilli; Franco Salvatore; Amalia Procida; Antonio Esposito (Journal of Biomedical Practitioners, 2023)
INTRODUCTION